Cross-country variation in household access to financial services - Honohan, Patrick (Journal of Banking & Finance, 2008)
This paper presents estimates, for more than 160 countries, of the fraction of the adult population using formal financial intermediaries. The estimates are constructed by combining information on account numbers at banks and microfinance institutions (together with banking depth and GDP data) with estimates from household surveys for a smaller set of countries. An illustrative application of the data compares them with information on poverty: there is a correlation, but it is not clearly causal.